Sprinkler irrigation on clay soils in southern Finland III. Effect on the quality of grain yield - Paavo Elonen; Lasse Nieminen; Osmo Kara (Agricultural and Food Science, 1967)
In the present paper the effect of irrigation on the ripening and on the quality of grain yield in the dry summers 1964—1966 was studied. Both the ripening and the quality of grain were found to be highly dependent on the date of irrigation. There was a distinct transitional period, before which irrigation speeded up ripening, decreased the amount of green grains and improved hectoliter weights and »falling numbers». On the contrary, if irrigation was applied after this transitional period, ripening was retarded and the quality of grains was impaired in regard to these properties. This transitional period was in the experimental years about two weeks before ear emergence or about Midsummer. The optimum period of irrigation, in regard to both yield level and to its ripening and quality, was in the middle between sprouting and ear emergence and its length was about two weeks. Wheat, barley and oats all responded to the date of irrigation in about the same way. The placement of fertilizers into the depth of 8—12 cm speeded up ripening and improved hectoliter weights. Particularly, it decreased the unfavourable effect of too late irrigation. The rate of fertilizers had no great influence on the quality of grains. Irrigation did not increase the weight of grains, but it increased the number of grains. The main effect of irrigation was likely to be caused by the tillering of crops, and these adventitious shoots had time to ripen, if irrigation was applied at a sufficiently early stage of development. The crude protein content of both wheat, barley and oats was markedly decreased by irrigation independently of the date of it. This decrease was usually the greater the higher yield was obtained. The decrease in the crude protein content indicates a shortage of nitrogen which was likely to be caused by the scanty mobilizeable resources of nitrogen in the soils long cultivated without leys. Obviously, this unfavourable decrease in the crude protein content could have been prevented with heavy dressings of fertilizer nitrogen.